The role of green products in enhancing the quality of life: An empirical study of organic food consumption among students of marketing department - Eneizan, Bilal (International Journal of Psychosocial Rehabilitation, 2020)
Improving quality of life is an important motivation for the consumption of organic foods. The aim of this study was to clarify the effect of organic food consumption on the quality of life. A questionnaire was adopted based on the literature review and distributed among the students of the marketing department. The sample of the study consists of 65 participants. The findings indicated that improving quality of life for the students is an important aspect of organic food consumption. The findings indicated that quality of life is influenced by organic food consumption. This study provides information about the importance of organic food consumption in improving the quality of life for students, especially in the places that use heavy usage of chemical fertilizers and harmful pesticides on the crops.